Data Profile of Lipoma and Liposarcoma at the Anatomical Pathology Laboratory of Siloam MRCCC Semanggi Cancer Hospital Jakarta - Gultom, Fajar Lamhot; Simanjuntak, Jonathan Savero; Angreni, Frisca (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Soft tissue tumors arise from mesenchymal tissues, with lipoma and liposarcoma being common types derived from adipose tissue. Considering the increasing prevalence of tumors in Jakarta, updated data on these specific cases are essential for better diagnostic and preventive measures. Objective: This study aims to determine the data profile of lipoma and liposarcoma patients at the Anatomical Pathology Laboratory of Siloam Cancer Special Hospital MRCCC Semanggi Jakarta during 2018–2019. Method: This research used a descriptive method with a cross-sectional approach. Data were collected from secondary medical records of all patients diagnosed with lipoma and liposarcoma at the laboratory. Result and Discussion: The study identified 56 cases in total, consisting of 52 cases of lipoma (92%) and 4 cases of liposarcoma (8%). Lipoma was predominantly found in patients aged 40–60 years, consistent with global epidemiological trends, while liposarcoma cases remained rare but clinically significant due to their malignant nature. Conclusions: Lipoma is significantly more prevalent than liposarcoma at this facility. These findings provide baseline data for clinical management and further epidemiological studies in specialized cancer hospitals in Indonesia